Risk of cardiac-related death in astrocytoma patients treated with chemotherapy: A competing risk analysis using the SEER database - Wang, Xuezhen; Li, Xiaoxia; Wu, Yufan; Hong, Jinsheng; Chai, Dajun; Zhang, Mingwei (Frontiers in Cardiovascular Medicine, 2023)
Purpose: To explore the impact of chemotherapy on the risk of cardiac-related death in astrocytoma patients. Methods: We retrospectively evaluated astrocytoma patients diagnosed between 1975 and 2016 in the Surveillance, Epidemiology, and End Results (SEER) database. Using Cox proportional hazards models, we compared the risks of cardiac-related death between a chemotherapy group and non-chemotherapy group. Competing-risks regression analyses were used to evaluate the difference in cardiac-related death. Also, propensity score matching (PSM) was employed to reduce confounding bias. The robustness of these findings was evaluated by sensitivity analysis, and E values were calculated. Results: A total of 14,834 patients diagnosed with astrocytoma were included. Chemotherapy (HR = 0.625, 95%CI: 0.444–0.881) was associated with cardiac-related death in univariate Cox regression analysis. Chemotherapy was an independent prognostic factor for a lower risk of cardiac-related death before (HR = 0.579, 95%CI: 0.409–0.82, P = 0.002) and after PSM (HR = 0.550, 95%CI: 0.367-0.823 P = 0.004). Sensitivity analysis determined that the E-value of chemotherapy was 2.848 and 3.038 before and after PSM. Conclusions: Chemotherapy did not increase the risk of cardiac-related death in astrocytoma patients. This study highlights that cardio–oncology teams should provide comprehensive care and long-term monitoring for cancer patients, especially those with an increased risk of cardiovascular disease.